Strategy of the Subang Regency Education and Culture Office in Improving Access and Quality of Basic Education in Remote Areas - Andani, Diah; Rakhmayudhi (International Journal of Science and Society, 2025)
This study aims to analyze the strategies implemented by the Department of Education and Culture of Subang Regency in improving access to and the quality of basic education in remote areas. The research adopts a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that the Department of Education and Culture of Subang Regency has implemented various strategies to enhance access to and the quality of basic education in remote regions, focusing on strengthening infrastructure, improving teacher quality, utilizing technology, and providing educational assistance. Despite ongoing challenges such as limited budgets, low community participation, and a shortage of qualified educators, the strategies implemented have begun to show positive impacts, particularly in increasing school participation and raising community awareness of the importance of education. A collaborative and adaptive approach to local conditions has proven to be a key factor in the success of efforts to improve the quality of education in areas that have long been underserved by formal education services.